Anemia and COVID-19 - Gürsoy, Vildan; Avcı, Suna; Ermurat, Selime; Erol, Ali; Yazıcı, Melike (The European Research Journal, 2023)
Objectives: Coronavirus disease-19 (COVID-19) is an infective-inflammatory disease that mainly affects the lungs. Hematological symptoms such as thrombocytopenia, decreased eosinophil and lymphocyte counts are quite common and are of prognostic importance. Although it is known that the presence of anemia generally increases the severity of respiratory diseases, there is little data on the prevalence and importance of anemia in COVID-19. In this study, our aim is to evaluate the clinical features of patients with anemia in COVID-19 infection and to investigate the relationship between the presence of anemia and the prognosis of the disease. Methods: This retrospective, observational study included 353 patients who presented to our pandemic reference hospital between 15.04.2020 and 15.05.2020 and were diagnosed with SARS-CoV-2 infection confirmed by real-time reverse transcription polymerase chain reaction (PCR) test and typical clinical symptoms. Results: Our study included 167 female and 186 male patients. The mean age was 54.54 ± 18.28 years (range 19-99). One hundred forty-eight (41.93%) patients had anemia. In patients with anemia, age was higher than others (p < 0.001). The percentage of women was significantly higher in the anemia group (p < 0.001). Comorbidities were observed more in the anemia group. The percentages of intensive care stay (p = 0.003) and mortality (p = 0.001) were significantly higher in the anemia group compared to the group without anemia. Logistic regression analysis was performed to determine the important risk factors of death. We found patients with high age (p = 0.001), high red cell distribution width-coefficient of variation (RDW-CV) levels (p = 0.009), high D-dimer levels (p = 0.012) and high ferritin levels (p < 0.001) have higher risk of death. Anemia was found to be non-significant. Conclusions: Anemia is frequently observed in patients with severe COVID-19 disease and low hemoglobin values at presentation are thought to be associated with a worse prognosis. Being more sensitive to the hemoglobin levels of COVID-19 patients is important for early recognition of the high-risk patient group and for successful patient management. However, in our study, the presence of anemia was found to be effective in mortality in univariate analysis, but not in multivariate analysis. According to the multivariate analysis of this study, advanced age, high D-dimer, high ferritin and RDW-CV determine death.